Single-molecule chemistry studied using the protein pore -α-hemolysin - Choi, LS (2012)
Single-molecule detection has provided insights into how molecules behave. Without the averaging effect of ensemble measurements, the stochastic behaviour of single molecules can be observed and intermediate steps in multistep transformations can be clearly detected. The single-molecule reactants range from small molecules (e.g. propene) to proteins of several tens of kDa (e.g. myosin). One single-molecule detection technique is single-channel electrical recording. This approach is based on the measurement of the transmembrane ionic current flowing through a nanoscale transmembrane pore under an applied potential. In this thesis, the protein α-hemolysin was employed as a nanoreactor. α-Hemolysin is a toxin secreted by Staphylococcus aureus. Its transmembrane pore (~100 Å in length and ≥14 Å in diameter) allows ions, water and small molecules to pass through its lumen. Under an applied potential, chemical changes in reactants attached to the internal wall of the pore modulate the flow of ions, leading to changes in the transmembrane ionic current. Analysis of this current provides information about the reaction kinetics and mechanisms. Chapter 1 – Single-Molecule Chemistry and α-Hemolysin is an introductory chapter that is divided into two parts. Section 1.1 provides an overview of the different techniques for the detection of chemical reactions at the single-molecule level. Section 1.2 gives a brief review of the protein pore α-hemolysin, including its structure, properties and various applications. Chapter 2 – S-Nitrosothiol Chemistry applies cysteine-containing α-hemolysins to study the biologically relevant chemistry of S-nitrosothiols (RSNO). RSNO are important molecules involved in cell signalling, which control physiological processes such as vasodilation and bronchodilation. Three reactions, namely transnitrosation (the transfer of the ‘NO’ group from RSNO to a thiol), S-thiolation (the formation of a disulfide from RSNO and thiol) and S-sulfonation (the generation of an S-sulfonate (RSSO₃⁻) from RSNO and sulfite ion), were investigated at the single-molecule level. The pH-dependency of the two competing reactions (transnitrosation and S-thiolation), the lifetime of the proposed transnitrosation intermediate, and nature of the chemical reaction between RSNO and sulfite (a bronchoconstrictor) were determined. Chapter 3 – Silver(I)-thiolate and cadmium(II)-thiolate complexes describes the kinetics of the formation and breakdown of these two metal-thiolate complexes. Ag⁺ and Cd²⁺ are commonly used in probing the membrane topology and gating properties of ion channels using the scanning cysteine accessibility method (SCAM). The binding of two Ag⁺ ions per thiol group and the stepwise build-up and dissociation of Cd²⁺-glutathione complexes were unambiguously characterized. Chapter 4 – Copper(II)-Catalyzed Diels-Alder Reactions reports the attempt to carry out copper(II)-catalyzed Diels-Alder reactions inside an engineered α-hemolysin. An iminodiacetate ligand was covalently attached within the lumen of the α-hemolysin pore. This ligand chelates Cu²⁺ ion, which can bind bidentate dienophiles and activate them towards Diels-Alder reaction with dienes. However, due to the ‘slow’ reaction rate of the Diels-Alder reaction (rate constant ~10⁻¹ M⁻¹s⁻) relative to the time-scale of the single-molecule experiment, we failed to observed chemical conversion at the single-molecule level. Nevertheless, the engineered metal-binding α-hemolysin may be useful for sensing molecules bearing metal-coordinating groups.